Fundamentals of information technology - BHARIHOKE, Deepak (New Delhi : Excel Books, 2002)
Presents a self-contained introduction to computers and computing. This book aims to provide an understanding of fundamental concepts of computer and computing technologies.
Keywords: Information technology. -- Textbooks; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management